2019
DOI: 10.1088/1755-1315/301/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Processing feasibility and qualities of freeze dried mango powder for SME scale

Abstract: This research studied the processing feasibility and quality of the premium mango powder ‘Mahachanok’ for SME business. Freeze-dried mango powder as alternative high quality mango powder. The frozen mango puree was thawed at 4°C for 12 hours. The freeze dry processes to freezing and vacuum drying product within a single chamber. The operation cycle included 3 main steps: First step was rapidly frozen with contact plate and air blast freezing at -50°C until core product temperature was -20°C. After that, two st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…To have a better understanding, data of each experiment were analyzed and varied physical phenomena were studied. In our experiments, we had no fixed shaft (Mawilai, Chaloeichitratham, & Pornchaloempong, 2019) temperature; it was continuously monitored with a thermocouple. As earlier discussed by many authors, the endpoint of primary drying is observed when the temperature of the shaft matches the product temperature.…”
Section: Resultsmentioning
confidence: 99%
“…To have a better understanding, data of each experiment were analyzed and varied physical phenomena were studied. In our experiments, we had no fixed shaft (Mawilai, Chaloeichitratham, & Pornchaloempong, 2019) temperature; it was continuously monitored with a thermocouple. As earlier discussed by many authors, the endpoint of primary drying is observed when the temperature of the shaft matches the product temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Processed mango has the potential to be used in the industry for applications in the food, cosmetics, and nutrition sectors, among others [20], due to the diversity of presentations that dehydration allows in a material supported by other operations such as spraying and sieving.…”
Section: Products and Applicationsmentioning
confidence: 99%
“…To preserve the color, phenolic compounds, and antioxidant capacity of heat-sensitive samples such as mango, it is suggested not to exceed ambient temperature in the last stage of freeze-drying [34]. In the literature, it was usually worked up to values of 10, 20, and 25 °C [29,58,62] with a maximum thermal increase of 40 °C [20].…”
Section: Preprintsmentioning
confidence: 99%
See 2 more Smart Citations